Microfluidic reactors for paired electrosynthesis: Fundamentals, applications and future prospects - Hao Xue; Zhi-Hao Zhao; Menglei Yuan; Guangjin Zhang (Green Energy & Environment)
Paired electrosynthesis has received considerable attention as a consequence of simultaneously synthesizing target products at both cathode and anode, whereas the related synthetic efficiency in batch reactors is still undesirable under certain circumstances. Encouragingly, laminar microfluidic reactor offers prospective options that possess controllable flow characteristics such as enhanced mass transport, precise laminar flow control and the ability to expand production scale progressively. In this comprehensive review, the underlying fundamentals of the paired electrosynthesis are initially summarized, followed by categorizing the paired electrosynthesis including parallel paired electrosynthesis, divergent paired electrosynthesis, convergent paired electrosynthesis, sequential paired electrosynthesis and linear paired electrosynthesis. Thereafter, a holistic overview of microfluidic reactor equipment, integral fundamentals and research methodology as well as channel extension and scale-up strategies is proposed. The established fundamentals and evaluated metrics further inspired the applications of microfluidic reactors in paired electrosynthesis. This work stimulated the overwhelming investigation of mechanism discovery, material screening strategies, and device assemblies.